(untitled) (Philadelphia, 2001)
This knowledge-packed resource provides a comprehensive yet concise review of primary-care information for students and clinicians preparing for the Certification (PANCE) and Recertification (PANRE) examinations. Readers can complete a "rapid review" of the material and test their knowledge with chapter self-assessments and a complete examination featured at the end of the book and on CD-ROM. Authored by leaders in PA education and clinical practice, this complete review book follows a systems approach, highlighting major components of each disease. Separate chapters cover pediatric disorders, infectious diseases, HEENT disorders, surgery disorders, and much more
Keywords: Physicians’ assistants,Clinical medicine,Physician Assistants